2004
DOI: 10.1207/s15374424jccp3301_10
|View full text |Cite
|
Sign up to set email alerts
|

Toward Effective Quality Assurance in Evidence-Based Practice: Links Between Expert Consultation, Therapist Fidelity, and Child Outcomes

Abstract: This study validated a measure of expert clinical consultation and examined the association between consultation, therapist adherence, and youth outcomes in community-based settings. Consultant adherence to the multisystemic therapy (MST) consultation protocol was assessed through therapist reports, and therapist adherence to MST principles was assessed through caregiver reports in 2 samples of families (N1 = 178, N2 = 274) and therapists (N1 = 87, N2 = 162). Caregiver reports of youth behavior and functioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(147 citation statements)
references
References 20 publications
4
143
0
Order By: Relevance
“…County leaders from the mental health, child welfare and juvenile justice systems were recruited to participate because studies have shown that successful incorporation of researchbased interventions require changes in existing policies, procedures, and practices (Olds et al 2003;Schoenwald et al 2004). Upon notification of study funding, the CiMH investigators emailed then sent a letter to the system leaders in all eligible counties notifying them that the grant was underway and inviting them to participate in the study.…”
Section: Recruitmentmentioning
confidence: 99%
“…County leaders from the mental health, child welfare and juvenile justice systems were recruited to participate because studies have shown that successful incorporation of researchbased interventions require changes in existing policies, procedures, and practices (Olds et al 2003;Schoenwald et al 2004). Upon notification of study funding, the CiMH investigators emailed then sent a letter to the system leaders in all eligible counties notifying them that the grant was underway and inviting them to participate in the study.…”
Section: Recruitmentmentioning
confidence: 99%
“…The intention of staff evaluation is to assess the use and outcomes of skills therapists are taught in training and help them continue to improve their effectiveness with patients [21,36,37]. Evaluating therapist performance and using fidelity measures, provides useful feedback concerning implementation efforts, training, and supervision.…”
Section: Future Developmentmentioning
confidence: 99%
“…Research suggests that coaching is effective at (a) increasing consultee knowledge; (b) strengthening both consultants' and consultees' skills (e.g., Capella et al, 2012;Miller, Yahne, Moyers, Marinez, & Pirritano, 2004); and (c) improving youth outcomes (e.g., Capella et al, 2012;Mashburn, Downer, Hamre, Justice, & Pianta, 2010;Schoenwald, Sheidow, & Letourneau, 2004). Theoretically, these successes are attributable to improved treatment integrity, which is the degree to which consultees implement an intervention as intended (Noell et al, 2000).…”
Section: Consultation and Coachingmentioning
confidence: 99%
“…Theoretically, these successes are attributable to improved treatment integrity, which is the degree to which consultees implement an intervention as intended (Noell et al, 2000). For example, coaching appears to result in increased consultee adherence to EBP protocols (Becker, Bradshaw, Domitrovich, & Ialongo, 2013;Schoenwald et al, 2004;Solomon, Klein, & Politylo, 2012), at least while coaching is underway. Still, more research is needed to clarify how consultation/coaching efforts improve the implementation of EBPs in schools.…”
Section: Consultation and Coachingmentioning
confidence: 99%